2020
DOI: 10.1371/journal.pone.0241263
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic features and mortality of individuals on haemodialysis treatment who test positive for SARS-CoV-2: A UK Renal Registry data analysis

Abstract: Kidney disease is a recognised risk factor for poor COVID-19 outcomes. Up to 30 June 2020, the UK Renal Registry (UKRR) collected data for 2,385 in-centre haemodialysis (ICHD) patients with COVID-19 in England and Wales. Overall unadjusted survival at 1 week after date of positive COVID-19 test was 87.5% (95% CI 86.1–88.8%); mortality increased with age, treatment vintage and there was borderline evidence of Asian ethnicity (HR 1.16, 95% CI 0.94–1.44) being associated with higher mortality. Compared to the gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
45
2
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 20 publications
3
45
2
6
Order By: Relevance
“…Our study con rmed the signi cant association of older age and death, which is also aligned with the ndings of the European ERACODA study [24]. Age was also identi ed as a risk factor for higher mortality in studies from the UK Renal Registry, from Japan and Spain [16,15,22]. On top of age, the ERA-EDTA study that included 3285 patients found male patients at higher risk for death [25].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our study con rmed the signi cant association of older age and death, which is also aligned with the ndings of the European ERACODA study [24]. Age was also identi ed as a risk factor for higher mortality in studies from the UK Renal Registry, from Japan and Spain [16,15,22]. On top of age, the ERA-EDTA study that included 3285 patients found male patients at higher risk for death [25].…”
Section: Discussionsupporting
confidence: 87%
“…In the largest Chinese sample from Wuhan, death rate was estimated at 20% [13]. The Paris Region, Japan, the UK Renal Registry, the Scottish Renal Registry, the Belgian Society of Nephrology, Brazil, Germany, Italy, Spain and New York reported death rates in hemodialysis of 27.3%, 16% (at one week), 12.5%, 26.7%, 29.6%, 27.7%, 26.8%, 32%, 20% and 27% respectively [14][15][16][17][18][19][20][21][22][23]. Recently, the largest two studies conducted in Europe, the ERACODA (European Renal Association COVID-19 Database) and the ERA-EDTA Registry reported a death rate after 28 days of follow-up of 25% and 20% respectively [24,25].…”
mentioning
confidence: 99%
“…The increased incidence of SARS-CoV-2 infection and increased mortality when infected have resulted in widespread death, with 1 in 33 ICHD patients in the United Kingdom dying from COVID-19 in the first wave. 5 Population-based analysis shows age-matched relative risk of death from COVID-19 for an ICHD patient compared with the general population ranges from 432 for a 20-to 39-year-old patient to around 10 for a patient aged >80 years. 5 To date, therefore, there is clear evidence that nonelderly patients on dialysis have experienced exceptionally high mortality rates, in most cases equaling or exceeding rates observed in elderly patients in their regions (i.e., those aged >80 years), who (properly) have generally been given priority for vaccination.…”
mentioning
confidence: 99%
“…5 Population-based analysis shows age-matched relative risk of death from COVID-19 for an ICHD patient compared with the general population ranges from 432 for a 20-to 39-year-old patient to around 10 for a patient aged >80 years. 5 To date, therefore, there is clear evidence that nonelderly patients on dialysis have experienced exceptionally high mortality rates, in most cases equaling or exceeding rates observed in elderly patients in their regions (i.e., those aged >80 years), who (properly) have generally been given priority for vaccination. There is a common misconception that most dialysis patients are very elderly and thus will automatically qualify for immediate vaccination.…”
mentioning
confidence: 99%
See 1 more Smart Citation